1998
DOI: 10.1007/pl00005278
|View full text |Cite
|
Sign up to set email alerts
|

Influence of depolarization on vasorelaxant potency and efficacy of Ca2+ entry blockers, K+ channel openers, nitrate derivatives, salbutamol and papaverine in rat aortic rings

Abstract: We examined the effects of various KCl concentrations on the actions of some vasodilators belonging to different pharmacological classes in rat aortic rings. In some experiments, tissues were precontracted with noradrenaline after blocking voltage-dependent channels to assess the effects of depolarisation unaccompanied by the entry of extracellular Ca2+ into the cytosol. Concentration/response curves for the vasorelaxant effect of calcium entry blockers (e.g. diltiazem), K+ channel openers (e.g. aprikalim), ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 39 publications
(46 reference statements)
2
17
0
Order By: Relevance
“…obs. ], as documented by other investigators [30]. Interestingly, the hyperpolarizing effects of pinacidil were greater in the aorta than in mesenteric arteries, and the resting membrane potentials were more positive in the aorta than in the mesenteric arteries.…”
Section: Discussionsupporting
confidence: 63%
“…obs. ], as documented by other investigators [30]. Interestingly, the hyperpolarizing effects of pinacidil were greater in the aorta than in mesenteric arteries, and the resting membrane potentials were more positive in the aorta than in the mesenteric arteries.…”
Section: Discussionsupporting
confidence: 63%
“…60 m M ) KCl concentrations, owing to – inter alia – the decrease of the chemical K + gradient accounting for the outward flow of K + , (+/−)‐naringenin and naringin were also tested on 60 m M KCl precontracted vessels. Indeed, their vasorelaxant activity was markedly depressed at high concentrations of K + (60 m M KCl), a finding compatible with the pharmacodynamic pattern typical of the K + channel openers (Magnon et al ., 1998). In a recent study on intact aorta rings, the vasorelaxant effect of (+/−)‐naringenin was shown to be mediated, at least in part, by endothelium released nitric oxide (Ajay et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the degree of depolarization of the vessel is an important consideration. 13) Isoquinolines have been shown to act on mureceptors. 2) Activated mu-receptors can delay neurotransmission and produce an analgesic effect.…”
Section: Discussionmentioning
confidence: 99%